Inovasi Prototipe E-Komik Jelajah Karier Dream Team Holland: Uji Validitas dan Kepraktisan - Ramadani, Herli; Pandang, Abdullah; Fitriana, Fitriana (Indonesian Journal of School Counseling: Theory, Application, and Development, 2025)
This study aims to develop a digital comic information media entitled "Career Exploration: Dream Team Holland" which can be used in guidance and counseling services to provide career information to students. This study uses a research and development method with a modified ADDIE model, consisting of stages of analysis, design, development, implementation, and evaluation. Data collection techniques use questionnaires and interviews, while data analysis techniques use quantitative and qualitative descriptive analysis. The results of this study are in the form of a prototype of the Dream Team Holland Career Exploration E-Comic which is developed including a user guide, a story with three main topics related to the selection of extracurricular activities, secondary schools, and professions that are tailored to personality types. The level of validity of the media based on the assessment of material experts reached 93% and 95%, and from media experts 80% and 98%. The practicality test by guidance and counseling teachers obtained a score of 84% and from students 90%. Based on these results, the developed e-comic media is declared valid and practical as a career information media for students at the junior high school level.